Aortic root replacement for bicuspid aortopathy following heart transplantation. Issue 10 (27th September 2017) - Stephens, Elizabeth H.; Fukuhara, Shinichi; Neely, Robert C.; Takayama, Hiroo
Abstract: Although donors with well‐functioning bicuspid aortic valves (BAV) are not a contraindication for transplantation, BAV patients are at risk for long‐term aortopathy and valve dysfunction. We report a case of a patient status‐post heart transplant 13 years ago who presented to our institution with a BAV and severe aortic regurgitation associated with an aortic root aneurysm and underwent aortic root replacement.